الاحتراق النفسي لدى المدربين الرياضيين كظاهرة سيكولوجية، والأسس النظرية لبناء برنامج إرشادي وقائي (Comprehensive Journal of Science, 2025)
The profession of sports coaching is a high-pressure environment where the chronic accumulation of occupational demands (such as pressure for results and job insecurity) leads to elevated rates of the Burnout Syndrome among coaches. This study illuminates this phenomenon as a three-dimensional psychological construct (Emotional Exhaustion, Depersonalization, and Reduced Personal Accomplishment), grounding its analysis in the Job Demands-Resources Model (JD-R Model) to establish the etiological factors of burnout. The study aims to bridge the theoretical gap in Arabic literature by designing a comprehensive theoretical framework for a preventive counseling program, based on an Integrative Counseling approach. This framework proposes merging two key theories: Cognitive Behavioral Therapy (CBT) to address irrational cognitions linked to Reduced Personal Accomplishment, and Mindfulness to enhance emotional regulation and reduce Emotional Exhaustion and Depersonalization. The study confirms that the proposed program, in its theoretical capacity, represents a systematic step towards equipping coaches with necessary psychological resilience and restoring self-efficacy, making it highly recommended as a theoretical reference for developing sustainable psychological support programs within sports organizations.